Treatment of dysphagia after stroke with acupuncture and related therapies: A protocol for systematic review and network meta-analysis. Issue 34 (21st August 2020) - Xiong, Fanjie; Song, Kai; Huang, Ailing; Zhang, Hong
Abstract: Background: Dysphagia is a common complication after stroke, with high disability rate and high fatality rate. Although several clinical studies and evidence-based medicine have demonstrated the efficacy of acupuncture in the treatment of dysphagia after stroke, there are significant differences in study design and intervention methods. The objective of this study is to compare the efficacy and safety of different acupuncture and related therapies in the treatment of dysphagia after stroke, so as to provide a superior clinical program. Methods: We will search 7 databases for randomized controlled trials of acupuncture-related therapies for dysphagia after stroke, including PubMed, the Cochrane Library, EMbase, China National Knowledge Infrastructure, China Biological Medicine, Chinese Scientific Journals Database, and wan-fang databases, from the date of the establishment of each database to March 31, 2020. The network meta-analysis will be implemented through Aggregate Data Drug Information System 1.16.8 and Stata 13.0 software. Clinical Efficiency, videofluoroscopic swallowing study score and Kubota Drinking Water Test grade will be the primary outcomes, Swallowing disorder specific quality of life score, Standardized Assessment and Adverse effects will be evaluated as secondary outcomes. Mean differences or odds ratios will be used for statistical analysis. We will ensure the reliability of the results through node-split model and heterogeneity analysis. In addition, methodological quality will be evaluated based on the Cochrane Collaboration's tool, and the quality of evidence will be evaluated according to the Grading of Recommendations Assessment, Development and Evaluation system. Results: This study will provide a reliable evidence for the selection of acupuncture and related therapies for dysphagia after stroke. Conclusion: The results of this study will provide references for evaluating the influence of acupuncture and related therapies for dysphagia after stroke, and provide decision-making references for clinical research. Ethics and dissemination: This study did not require ethical approval. We will disseminate our findings by publishing results in a peer-reviewed journal. OSF registration number: DOI 10.17605/OSF.IO/TAHND.